Register, cap and trade: A proposal for containing systemic liquidy risk - Alistair Milne (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
A fundamental cause of the global financial crisis was excessive maturity mismatch, notably shadow banking holdings of sub-prime MBS and other structured credit instruments and cross-border Euro area interbank lending to the uncompetitive Euro area periphery. The costs of short term funding do not fully reflect underlying asset risks and this created systemic liquidity and credit risks. This externality can be controlled through the issue of tradable licenses for short term funding. This is a simpler and more efficient way of addressing systemic liquidity risk than the controls on individual institutions proposed by international regulators.
Keywords: G28; E44; G21; 330; Basel III; debt deflation; endogenous money; financial regulation; global financial crisis; limited purpose banking; maturity mismatch; narrow money; Pigouvian taxes; ring fencing; systemic financial risk; systemic financial externalities; Tobin tax; Geldsubstitut; Finanzmarktkrise; Regulierung; Basler Akkord; Hybrides Finanzprodukt; Finanzderivat; Welt